Impacts of climate warming on atmospheric phase transition mechanisms - Varotsos, Costas A.; Ghosh, Satyajit (Theoretical and applied climatology, 2017)
Nowadays, climate change is a fact, and its impacts on heterogeneous chemistry mechanisms that take place in various atmospheric layers are of great interest. As an example, the uptake of atmospheric species on solid and liquid surfaces induces qualitative and quantitative changes from climatic alterations of the atmospheric thermal regime. We hereby present the experience gained on this subject by analysing real measurements of various atmospheric species and parameters conducted in Athens, Greece, exploring the atmospheric height region from the Earth’s surface up to the lower stratosphere.